Hidrolisis Pati Garut Secara Enzimatis untuk Pembentukan Siklodekstrin - Erliza Noor (Institut Pertanian Bogor, 2008)
Modified starch has important role in chemical, cosmetic, pharmaceutical, and food industries. Cyclodextrin was prepared based on garut starch using starch hidroying enzime namely 0-amylase, 0-amylase, pullulanase and glukoamylase. Cyclication to form cyclodextrin was obtained using CGTase. The highest concentration of cyclodextrin was obtained by glucoamylase and CGTase concentration of 150 unit/g substrate which was 81.11g.l-1 in 90 minutes. Keywords: 0-amylase, 0-amylase, cyclodextrin, CGT-ase, gantt starch, glukoamylase, pullulanase